Art-Rite - Robinson, Walter; Cohn, Joshua (New York : Primary Information,Printed Matter, 2019)
This facsimile edition collects all 19 issues of 'Art-Rite' magazine, edited by art critics Walter Robinson and Edit DeAk from 1973 to 1978. Robinson, DeAk and a third editor, Joshua Cohn, met as art history students at Columbia University, and were inspired to found the magazine by their art criticism teacher, Brian O?Doherty. 'Art-Rite', cheaply produced on newsprint, served as an important alternative to the established art magazines of the period.0'Art-Rite' ran for only five years, and published only 19 issues. But in that time the magazine featured contributions from hundreds of artists, a list that now reads like a who?s-who of 1970s art: Yvonne Rainer, Gordon Matta-Clark, Alan Vega (Suicide), William Wegman, Nancy Holt, Jack Smith, Dorothea Rockburne, Robert Morris, Adrian Piper, Laurie Anderson, Carolee Schneemann and Carl Andre; critics such as Lucy Lippard contributed writing. Through its single-artist issues and its thematic issues on performance, video and artists? books, 'Art-Rite' championed the new art of its era.
Imported from: zcat.oclc.org:210/OLUCWorldCat (Do not remove)
boek